2015
DOI: 10.3389/fnmol.2015.00012
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium dynamics in cortical microglia responding to focal laser injury in the PC::G5-tdT reporter mouse

Abstract: Microglia, the resident immune cells of the brain parenchyma, are highly responsive to tissue injury. Following cell damage, microglial processes redirect their motility from randomly scouting the extracellular space to specifically reaching toward the compromised tissue. While the cell morphology aspects of this defense mechanism have been characterized, the intracellular events underlying these responses remain largely unknown. Specifically, the role of intracellular Ca2+ dynamics has not been systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(121 citation statements)
references
References 38 publications
(48 reference statements)
9
106
0
Order By: Relevance
“…Many of the molecular pathways involved require intracellular Ca 2+ signaling and therefore changes in intracellular free Ca 2+ concentration ([Ca 2+ ] i ) might be able to provide an early and rather sensitive measure of microglial activation. Indeed, surveillant microglia in the healthy brain are known to maintain a low basal [Ca 2+ ] i accompanied by rare 'spontaneous' Ca 2+ transient increases in a minority of cells (Eichhoff, Brawek & Garaschuk, 2011;Pozner et al, 2015;. However, in vivo damage of even a single cell was shown rapidly (on a scale of milliseconds to seconds) and reliably to produce a so-called damage-associated [Ca 2+ ] transient in nearby microglia (Eichhoff et al, 2011).…”
Section: Morphological and Functional Signs Of Microglial Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the molecular pathways involved require intracellular Ca 2+ signaling and therefore changes in intracellular free Ca 2+ concentration ([Ca 2+ ] i ) might be able to provide an early and rather sensitive measure of microglial activation. Indeed, surveillant microglia in the healthy brain are known to maintain a low basal [Ca 2+ ] i accompanied by rare 'spontaneous' Ca 2+ transient increases in a minority of cells (Eichhoff, Brawek & Garaschuk, 2011;Pozner et al, 2015;. However, in vivo damage of even a single cell was shown rapidly (on a scale of milliseconds to seconds) and reliably to produce a so-called damage-associated [Ca 2+ ] transient in nearby microglia (Eichhoff et al, 2011).…”
Section: Morphological and Functional Signs Of Microglial Activationmentioning
confidence: 99%
“…This process was driven by ATP/ADP-induced P2Y 12 receptor signaling, activation of phospholipase C and Ca 2+ -dependent phosphorylation of serine/threonine kinase (Akt) as well as phosphoinositide-3-kinase (PI3K)-mediated Akt phosphorylation (Eichhoff et al, 2011;Madry & Attwell, 2015). Both acute and chronic (neuro)inflammation were shown to be accompanied by an increase in 'spontaneous' Ca 2+ signaling of microglia Pozner et al, 2015) again pointing to changes in microglial [Ca 2+ ] i as a universal hallmark of activated microglia.…”
Section: Morphological and Functional Signs Of Microglial Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we describe a series of observations regarding microglial calcium signaling in response to shifts in neuronal activity. In general, microglia are considered to have the lowest levels of spontaneous calcium activity in “resting” or “baseline” states from reports in anesthetized mice (Brawek et al, 2017; Eichhoff et al, 2011; Pozner et al, 2015). We observe that microglial calcium activity is similarly low in awake, chronic window mice.…”
Section: Discussionmentioning
confidence: 99%
“…Early work in situ suggested that calcium activity was critical for microglia, with calcium signaling underlying key physiological functions such as motility, cytokine release, and receptor trafficking/diffusion (Färber and Kettenmann, 2006; Korvers et al, 2016; Toulme and Khakh, 2012). However, more recent in vivo studies have demonstrated that spontaneous calcium signaling is nearly absent in microglia (Brawek et al, 2017; Eichhoff et al, 2011; Pozner et al, 2015). Such observations downplay the potential utility of calcium signaling for microglial function.…”
Section: Introductionmentioning
confidence: 99%